ORGANIZATIONAL RESOURCES AND STRATEGIC PLANS IMPLEMENTATION IN ADMINISTRATION POLICE SERVICE IN BARINGO COUNTY, KENYA - Ngumbi, Fedinard Mumo; Wambua, Dr. Philip (European Journal of Business and Strategic Management, 2019)
Purpose: The aim of the study was to explore the relationship between organizational resources and strategic plans implementation in Administration police service in Baringo County, Kenya. Methodology: The study adopted descriptive research design. The population of this study was administration police officers deployed in Baringo County. The total number of officers was 720 found in six sub counties; Baringo Central 92, Baringo North 113, Mogotio 81, Marigat 223, Koibatek 128 and East Pokot 83. The aggregate sample size was 216. Data was collected by use of structured questionnaires adopting Likert scale formation. Data was analyzed mainly by use of descriptive and inferential statistics. Descriptive statistics included mode, mean, median, standard deviation. Inferential statistical techniques like correlation and regression coefficients were used to draw causal relationship between the various organizational resources and implementation of strategic plans. Data was presented by use of graphs, pie charts and tables. Results: The study findings indicate that organizational resources significantly influenced implementation of strategic plans. Financial, human, capital and technological resources greatly influence successful implementation of strategic plans in an organization. Unique contribution to theory, practice and policy: The study recommended that there is need for increased funding of Administration police service in Baringo County both from the national and county governments. Job relationship between senior and junior officers should be improved. Government should ensure all housing facilities are operational, in good condition and enough. The study further recommends clear guidelines on implementation of reforms, community-based policing and improvement of guidelines on training, enhancement and capacity building.